(untitled) - Sevilleja, Ruben C. (Phillipines, 1995)
The study evaluated the financial feasibility of rice-fish farming using the pond refuge system as case exampla. Analysis of the product-product relationship for the determination of the maxium output combination of fish and rice was also done.
Keywords: Rice,Fish,Farm management